THE URGENCY OF FORMING A SPECIAL LAW FOR TAX CONSULTANTS AS A SUPPORTING PROFESSION FOR THE INDONESIAN FINANCIAL SECTOR: THE URGENCY OF FORMING A SPECIAL LAW FOR TAX CONSULTANTS AS A SUPPORTING PROFESSION FOR THE INDONESIAN FINANCIAL SECTOR - Deswanta, Andi; Hamid, Adnan; Akkapin, Supaphorn (PENA LAW: International Journal of Law, 2025)
Tax consultants as supporting professionals in the financial sector play a strategic role in Indonesia’s taxation system, yet face fundamental legal uncertainty. This research analyzes the legal status of tax consultants in Indonesia’s taxation system and formulates a comprehensive legal protection concept for the profession. The research method employs a normative juridical approach with regulatory analysis and literature study. The findings reveal that the legal status of tax consultants experiences a paradox where the profession obtains formal recognition through the General Tax Law and Ministerial Regulations but faces serious legal vulnerabilities in practice. Tax consultants are trapped in a dual status as independent professionals and taxpayer representatives without adequate legal protection, unlike advocates and public accountants who already have legislative umbrella laws. Dependence on ministerial-level regulations creates legal uncertainty exacerbated by professional organization fragmentation and criminalization threats. The comprehensive legal protection concept requires systemic transformation through establishing specific legislation that integrates preventive and repressive dimensions. Concrete mechanisms include legal immunity based on good faith, consolidation of unified professional organizations, and establishment of independent ethics councils. Harmonization with international practices will enhance professional credibility and support tax revenue optimization through a professional taxation ecosystem.